2006
DOI: 10.1001/archinte.166.21.2362
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Mitral Regurgitation and Risk of Heart Failure After Myocardial Infarction

Abstract: Background: The development of ischemic mitral regurgitation (MR) after myocardial infarction may impose hemodynamic load during a period of active left ventricular remodeling and promote heart failure (HF). However, few data are available on the relationship between ischemic MR and the long-term risk for HF. Methods: We prospectively studied 1190 patients admitted for acute myocardial infarction. Mitral regurgitation was assessed by echocardiography and was considered mild, moderate, and severe when the regur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 31 publications
7
73
2
4
Order By: Relevance
“…A similar increase in mortality over the longer term (five years) with ischaemic MR was reported 26 . Ischemic MR also predicts the development of HF in AMI patients with a little or no symptoms at baseline 119 and HF risk with moderate to severe MR was ~50% at two years in one series 120 .…”
Section: Role Of Echocardiography In Therapeutic Interventionsupporting
confidence: 63%
“…A similar increase in mortality over the longer term (five years) with ischaemic MR was reported 26 . Ischemic MR also predicts the development of HF in AMI patients with a little or no symptoms at baseline 119 and HF risk with moderate to severe MR was ~50% at two years in one series 120 .…”
Section: Role Of Echocardiography In Therapeutic Interventionsupporting
confidence: 63%
“…The ensuing chamber dilatation and neurohormonal activation lead to progressive LV dysfunction. 6 The presence of IMR further inflicts the hemodynamic load during a period of active LV remodeling. 7, 16 Aronson et al reported that there is a graded independent association between the severity of ischemic MR and the development of heart failure after MI.…”
Section: Discussionmentioning
confidence: 99%
“…7, 16 Aronson et al reported that there is a graded independent association between the severity of ischemic MR and the development of heart failure after MI. 6 Ishikawa et al reported ischemic MR to be a common cause of congestive heart failure, caused by the process of MI remodeling. 22 The present study further strengthens the context of LV remodeling in the presence of IMR, in that it eventually associates with a lower LVEF and a higher Killip score.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It is usually mild or moderate in severity but is associated with an increased incidence of heart failure and death. 1,2 It is caused by left ventricular (LV) remodeling and dilatation after myocardial infarction, which tethers and pulls the mitral valve apart, resulting in MR; the mitral valve is normal in structure but is incompetent as a result of a dilated and dysfunctional left ventricle. 3,4 The majority have significant 3-vessel coronary artery disease and benefit from coronary artery bypass grafting (CABG).…”
mentioning
confidence: 99%